Decreased RORC-dependent silencing of prostaglandin receptor EP2 induces autoimmune Th17 cells - Kofler, David M. (American Society for Clinical Investigation, 2014)
Prostaglandin E2 (PGE2) promotes Th17 expansion while otherwise inhibiting other CD4(+) T cell subsets. Here, we identified a PGE2-dependent pathway that induces pathogenic Th17 cells in autoimmune disease and is regulated by the transcription factor RORC. Compared with other CD4(+) cell types from healthy subjects, there is a surprising lack of the prostaglandin receptor EP2 on Th17 cells; therefore, we examined the hypothesis that RORγt, which is highly expressed in Th17 cells, mediates EP2 downregulation. Chromatin immunoprecipitation followed by DNA sequencing revealed that RORγt binds directly to Ptger2 (the gene encoding EP2 receptor) in Th17 cells isolated from WT mice. In Th17 cells isolated from humans, RORC repressed EP2 by directly silencing PTGER2 transcription, and knock down of RORC restored EP2 expression in Th17 cells. Compared with Th17 cells from healthy individuals, Th17 cells from patients with MS exhibited reduced RORC binding to the PTGER2 promoter region, resulting in higher EP2 levels and increased expression of IFN-γ and GM-CSF. Finally, overexpression of EP2 in Th17 cells from healthy individuals induced a specific program of inflammatory gene transcription that produced a pathogenic Th17 cell phenotype. These findings reveal that RORC directly regulates the effects of PGE2 on Th17 cells, and dysfunction of this pathway induces a pathogenic Th17 cell phenotype.